Developing Computer Course Models Based on Learning Management System for Early Children Education Teachers - ., Jamaluddin; ., Ummu Khaltsum; Muchtar, Fitriyanti (KnE Social Sciences, 2023)
Course and training institutions as a nonformal education unit organized for people who need knowledge, skills, life skills, and attitudes for self-development, professional development, work, independent business, and/or continuing education to a higher level. Currently, the world is faced with the phenomenon of digital disruption, which is a situation shown by the movement of the industrial world or job competition that is no longer linear. In the field of courses and training, the current era of disruption has also led to online course and training services that can be accessed via the service provider’s web/page. These service providers are not in the form of educational units, but several experts in their fields have joined forces with several experts in information and communication technology to create courses and training services that can be accessed through electronic devices such as computers, laptops, and communication devices. One of the development of courses and training in the field of information and communication technology is based on learning management system (LMS)—a webbased application system that allows instructors and/or students to share material, submit, and return assignments, and communicate online. Results of research and development of computer-based course models and training that have been tested shows that the level of practicality of this model is very good according to the instructor, course, and training organizers. Results of course learning and computer-based training can improve the skills of early childhood education teachers in the office application computer course program. Keywords: non-formal education, courses and training, learning management system, early childhood education teachers